The quality of nursing home care to dependent elderly - Carvalhais, Maribel; Sousa, Liliana (Saúde e Sociedade, 2013)
This exploratory study aims to contribute to the promotion of quality nursing home care to elderly people. Photovoice was adopted; it is a participatory method (qualitative) that uses photograph and voice to facilitate/mediate our access to the others world. The sample comprised 6 nurses aged from 24 to 30 years old, 5 females. Main findings suggest that the promotion of the quality of nursing home care to dependent elderly involves: i) work and decision in multidisciplinary team; ii) more material and human resources; iii) support to the informal caregivers (usually family members); iv) nurses' determined posture. The main obstacle concerns the shortage of resources and disorganization which are reflected on lack of time, disorder and frustration. The participants underlined the relevance of families' involvement, since they are part of the care unit.